209k views
10 votes

3x+9+2x=x-2x-3

User Den B
by
5.2k points

2 Answers

5 votes
9+5x=-x-3
9+6x=-3
6x=-12
X=-2
User HoRiz
by
5.1k points
7 votes

Answer:

Explanation:

Equation

3x + 9 + 2x = x - 2x - 3

Solution

Combine all the like terms.

3x+2x+9 = x - 2x - 3

5x + 9 = -x - 3 Add x to both sides of the equation

5x+x +9 = -x+x -3 Combine

6x + 9 = - 3 Subtract 9 from both sides of the equation

6x+9-9 = - 3-9 Combine

6x = -12 Divide both sides by 6

6x/6 = -12/6

x = - 2

Answer x = - 2

User Jzheaux
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.